A Short Satisfaction Questionnaire for an Independent Medical Examination: A pilot study. (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: pilot study; independent medical examination; satisfaction questionnaire; internal consistency; valida-tion; intrarater